2007
DOI: 10.1016/j.ejheart.2006.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained week‐to‐week variation in BNP and NT‐proBNP is low in chronic heart failure patients during steady state

Abstract: Background: The usefulness of brain-natriuretic-peptide (BNP) and N-terminal-pro-brain-natriuretic-peptide (NT-proBNP) for monitoring of chronic heart failure (CHF) patients has been questioned because of high levels of unexplained variation. Aims: Week-to-week total variance (CV T ), unexplained variation (CV I ), reference change values (RCV), index of individualities (IOI) and number of samples (N) with week-to-week intervals needed to estimate the underlying homeostatic set point (T15%) for BNP and NTproBN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 41 publications
(60 reference statements)
0
58
0
3
Order By: Relevance
“…The key to understanding these results is the rigidity of the definition of stability of heart failure. In studies that expended large efforts to ascertain stability (12,25,26 ) the CVs found were lower than in studies with less strict criteria (9,11 ). Consequently, we found The dotted lines indicate 1.96 ϫ SD of the mean of the differences (95% confidence with P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The key to understanding these results is the rigidity of the definition of stability of heart failure. In studies that expended large efforts to ascertain stability (12,25,26 ) the CVs found were lower than in studies with less strict criteria (9,11 ). Consequently, we found The dotted lines indicate 1.96 ϫ SD of the mean of the differences (95% confidence with P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 67%
“…Previous reported studies on short-or long-term variability found RCVs around 100% (8, 9 ) (11 ), others found CVs between 20% and 30% (10,12,13,25,26 ). The key to understanding these results is the rigidity of the definition of stability of heart failure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[2][3][4][5] While these studies have differed somewhat in their results, they have all been consistent in showing significant variability in values among patients with stable heart failure. A summary of these data would suggest that the reference change value (RCV) for BNP is approximately 50% and is modestly less for NTproBNP.…”
Section: Biologic Variability Of Natriuretic Peptide Valuesmentioning
confidence: 89%
“…Currently, there is no consensus on which approach (nANOVA or lognormal) to determining RCV is better. Data on biological variation of NT-proBNP have been published with markedly differing results (reviewed in [13]), mainly related to the use of data transformation, particularly in patients with chronic heart failure [14,15]. As component of variation is computed based on nANOVA, the distributional assumptions underlying the use of this method should be satisfied, which is not the case for skewed distributions, as NT-proBNP's.…”
Section: Introductionmentioning
confidence: 99%